Daily consumption of a homeopathic product decreases intestinal damage and stool bacterial counts in mice challenged with Escherichia coli - Jaguezeski A.M. (2020)
© 2020 Elsevier LtdEscherichia coli is a bacterium normally found in the gastrointestinal tract of domestic animals that can usually control the infection. Nevertheless, some factors (high exposure, stress conditions, animal category, among others) can favor the exacerbation of E. coli infection and cause of disease. Because it is a zoonotic bacterium, it is important to control the infection, avoiding contamination of home interiors in the case of pets. There are various forms of treatment for E. coli; nevertheless, there are few options for prevention. In the present study, we evaluated homeopathy. Thus, the objective of this study was to determine whether administration of a prophylactic homeopathic in water would minimize the negative effects of E. coli infection, as well as reducing bacterial counts in the feces of a experimental model. Forty mice were divided into four experimental groups (n = 10/group). Groups NC (negative control) and PC (positive control) were not treated; in group T1, the animals received 0.002 mL/day/animal of the homeopathic in water, and animals in group T2 0.004 mL/day/animal. The experiment lasted 54 days, and on the 31st day, mice of T1, T2 and PC groups were infected orally a 0.2 mL inoculum of 1.5 × 108 CFU of E. coli. Euthanasia and sample collection were performed on the 40th and 54th days of the experiment (n = 5/group/time point). Blood, liver, spleen, intestine, and feces samples were collected from the final portion of the intestine. There was no significant difference in animal weight between groups at the end of the experiment. Neutrophil count was lower in PC group animals on day 40, while on day 54, the counts were lower in T2 and PC. Lymphocyte counts were lower only in the PC group than in the NC group on day 54. Globulins were lower in the NC and PC groups than in T1 and T2 on day 40, remaining lower the PC group and higher in T1 on day 54; levels of immunoglobulin IgG and IgM were higher in groups T1 and T2, which differed from PC and NC. TNF-α levels were higher in the T1 and T2 groups at 40 and 54 days. INF-γ levels were higher in T1, T2, and PC compared to NC on day 40, remaining higher than NC in groups T1 and T2 on day 54. Total bacterial count, total coliforms and E. coli counts were lower in group T1 and higher in NC and PC on days 40 and 54, when they were lower for T1 and T2. Histologically, no lesions were observed in extra-intestinal tissues; however the height of intestinal crypts in the PC group was smaller than the others on day 40. On day 54, villi and crypts of all infected groups were larger in T1 and T2 than in NC; sizes in the PC group were higher than those of all other groups. These data suggest that the homeopathic agent in the drinking water improved health of the mice.